Picea schrenkiana Fisch. et C.A. Mey. in the Peter the Great Botanical Garden - Firsov Gennadiy; Volchanskaya Alexandra; Orlova Larisa; Tkachenko Kirill; Staroverov Nokolay; Gryaznov Artem (Hortus Botanicus)
Picea schrenkiana Fisch. et C.A. Mey. (Pinaceae) owes its introduction to the Peter the Great Botanical Garden BIN RAS to A.I. Shrenk, who made his first trip to Dzungaria in 1840. In this institution, it was first introduced into world culture. In decorative terms, it is interesting due to its narrow crown and bluish-green color of the needles. In the modern collection, the specimen at the age of 69 years reached 12.0 m in height. In 2022, under conditions of a warm growing season, it began to produce cones at the age of about 50 years. In the spring of 2023, seed offspring of their own reproduction were obtained for the first time. It is promising for further and wider cultivation at the North-West of Russia.